FAKTOR-FAKTOR YANG MEMENGARUHI KUALITAS AUDIT - Fitri Dwi Cahya Ningrum; Mahendro Sumardjo; Wisnu Julianto (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2022)
This study aims to examine the effect of audit tenure, public accounting firm size, audit fee, and client company size on audit quality. The sample in this study amounted to 63 financial sector companies listed on the Indonesia Stock Exchange in 2015-2019 using the purposive sampling method. Data form 63 companies obtained a total sample of 315. The analysis technique used is logistic regression analysis with a significance level of 5%. The results showed that audit tenure, fee audit, and client company size have no significant effect on audit quality. Meanwhile, public accounting firm size has a negative and significant effect on audit quality. Keywords: Audit Tenure; Public Accounting Firm Size; Fee Audit; Client Company Size; Audit Quality.